Mythological thought in jafar jabbarli’s creation. - Hashimova, Aybeniz (Universidad y Sociedad, 2023)
ABSTRACT Mythological thinking study is important because it helps us understand the world around us in a symbolic way, to interpret the events in our lives in a meaningful way helping us to make sense of the patterns and cycles that shape it. It can also help us to gain insight into our own motivations and actions and can provide us with a better understanding of our own identity. Azerbaijani mythology is very rich, and its expression in artistic works is very varied, but in our opinion the work of Jafar Jabbarli has a special place. Therefore, the objective of this work was to analyze the expressions of mythological thought in the work of Azerbaijani artist Jafar Jabbarli, specifically in the work “The Bride of Fire”. It is shown how the author formed concepts such as mythological symbol, chronotope and mythological thinking in the reader throughout his work improving the possibilities of mutual manifestation of the view of faith in written literature and national consciousness, precisely on the basis of ethnic consciousness. It is concluded that by basing the drama "Bride of Fire" on the model of myth, he did not aim to create an external effect, but first of all, he took the initiative to illuminate his ideas about man and his pain, joy, problems, spiritual and moral world in a different way. Keywords: "Bride of Fire", mythological symbol thinking, cosmological myth, artistic creativity RESUMEN El estudio del pensamiento mitológico es importante porque nos ayuda a comprender el mundo que nos rodea de forma simbólica, a interpretar los acontecimientos de nuestra vida de forma significativa, ayudándonos a dar sentido a los patrones y ciclos que le dan forma. También puede ayudarnos a comprender mejor nuestras propias motivaciones y acciones y puede proporcionarnos una mejor comprensión de nuestra propia identidad. La mitología azerbaiyana es muy rica y su expresión en obras artísticas es muy variada, pero en nuestra opinión la obra de Jafar Jabbarli tiene un lugar especial. Por ello, el objetivo de este trabajo fue analizar las expresiones del pensamiento mitológico en la obra del artista azerbaiyano Jafar Jabbarli, específicamente en la obra “La novia de fuego”. Se muestra cómo el autor formó conceptos como símbolo mitológico, cronotopo y pensamiento mitológico en el lector a lo largo de su obra, mejorando las posibilidades de manifestación mutua de la visión de la fe en la literatura escrita y la conciencia nacional, precisamente sobre la base de la conciencia étnica. Se concluye que al basar el drama "La novia de fuego" en el modelo del mito, no pretendió crear un efecto externo, sino que, ante todo, tomó la iniciativa de iluminar sus ideas sobre el hombre y su dolor, alegría, problemas, mundo espiritual y moral de una manera diferente. Palabras clave: "Novia de fuego", pensamiento de símbolos mitológicos, mito cosmológico, creatividad artística